An evolving data wise culture (DWC): A case study - Sun, Jingping; Levey, Joyce; Vaux, Nicole (Journal of Interdisciplinary Studies in Education, 2015)
Data-informed instructional decision-making has evolved into an essential processin schools. This feature has not been fully reflected in the school cultureconstructs developed to date. To reflect this feature, this study examines theextent to which a data-wise culture (DWC) exists in schools and test if theconstruct that reflects such a culture can be measured. The study finds that therewas such a culture existing in the schools in one district. The reliability of theconstruct DWC was high, indicating that the construct could be a unique variablethat deserves further exploration. The DWC survey can be used to evaluate howwell school leaders influence school conditions that foster data analysis inschools. This paper calls for the revisit of those cultural variables that have beendeveloped to date in the field of educational leadership to reflect the new featureof data use in schools.